The influence of information quality and innovation on satisfaction with perceived value as a mediating variable (a study of chatgpt plus users in Indonesia) - Alifiya Adhiya Asy Syifa; Ramadania Ramadania; Juniwati Juniwati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of information quality and innovation on ChatGPT Plus user satisfaction, with perceived value as a mediating variable. This study used a quantitative approach with a purposive sampling technique on 207 ChatGPT Plus user respondents in Indonesia. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 7.0. The results showed that information quality and innovation had a positive and significant effect on perceived value and user satisfaction. In addition, perceived value was proven to have a significant effect on satisfaction and acted as a mediating variable. These findings indicate that improving information quality and service innovation can increase perceived value and user satisfaction. Future research is recommended to add variables such as trust, ease of use, and user experience to enrich the research model.